2017
DOI: 10.1097/fpc.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 genotype distributions in the Korean population

Abstract: Thiopurines have a narrow therapeutic range because of frequent toxicity (i.e. marrow suppression), which is only partly explained by TPMT genetic polymorphisms, especially within Asian populations. Recent studies have identified NUDT15 variation as another important factor affecting thiopurine metabolism. In this study, a total of four NUDT15 coding variants (p.Arg139Cys, p.Arg139His, p.Val18Ile, and p.Val18_Val19insGlyVal) were genotyped in 920 Korean individuals using direct sequencing of NUDT15 for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 11 publications
2
30
1
Order By: Relevance
“…This finding was comparable to previous studies performed in Asian populations (variant allele frequency 2.3–5.0%) which was lower than for individuals of European descent . Meanwhile, in this study, the frequency of NUDT15 variant alleles was 14.0% which was comparable to a previous study in the Korean population . NUDT15 , another important gene with a similar pathway as TPMT , was first identified as a candidate gene by a genome‐wide association study (GWAS) of inflammatory bowel disease patients and in children with ALL .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding was comparable to previous studies performed in Asian populations (variant allele frequency 2.3–5.0%) which was lower than for individuals of European descent . Meanwhile, in this study, the frequency of NUDT15 variant alleles was 14.0% which was comparable to a previous study in the Korean population . NUDT15 , another important gene with a similar pathway as TPMT , was first identified as a candidate gene by a genome‐wide association study (GWAS) of inflammatory bowel disease patients and in children with ALL .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, two SNPs of NUDT15 (rs116855232 and rs186364861) were identified in association with thiopurine metabolites and therapeutic interruption which confirmed and reflected previous findings on its association with thiopurine‐related hematopoietic toxicity (Tables ). Because the frequency of the variant alleles range from 0.2–17.2% in different ethnic populations and the variant alleles are more common in East Asian populations, standard guidelines including thiopurine dosage adjustment on the basis of NUDT15 genotyping is needed for safe thiopurine therapy . In this study, patients with NUDT15 variants showed significantly lower 6‐TGN/6‐MP dose ratios (Figure ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Such drugs are purine analogues like anticancer and anti-gout drugs. During the last decade, the importance of NUDT15 is being appreciated and a strong association between thiopurine toxicity and this gene's polymorphisms in patients with Asian ethnicity has been reported (Moriyama et al, 2016;Kim et al, 2017;Singh et al, 2017). Even though the frequency of risk alleles in the European and African individuals is low, such studies were important to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the common missense variant NUDT15 :NM_018283.2:c.415C>T (Arg139Cys, dbSNP: rs116855232 T allele) conferred susceptibility to thiopurine-induced leukopenia in a genetic dose-dependent manner, with an odds ratio (OR) of 35.6 [16]. The finding has since been replicated in other patient populations, and has confirmed the prognostic value of NUDT15 c.415C>T genotyping in East Asian populations, where up to more than 20% of the population may be affected and require dose-adjustment or discontinuation [17]. …”
Section: Introductionmentioning
confidence: 99%